Shifting of Social Functions on Management of Foundation in Medan City - Sunarmi; Mirza Nasution; Zakiah (Jurnal Ilmiah Penegakan Hukum, 2023)
In founding the foundation there is also no uniformity. Notaries usually do not have a standard format regarding the founding deed of the foundation. As a result, each foundation can have its own articles of association as well as the Civil Society Association. Each foundation can make the articles of association according to their needs. The study was conducted using a normative juridical approach with the aim of obtaining secondary data, namely the inventory of legislation and data collection tools in the form of document studies. The foundation was established and developed with the family's efforts so that when the foundation developed rapidly and had many assets, the assets were owned by the family, family assets. The foundation is managed jointly by the family so that when a foundation regulation is established demanding changes to the Articles of Association, this means that there will be separation of foundation assets, restoration of the social functions of the foundation, transparency of accountability and publicity of the foundation's financial statements and ownership of the foundation belongs to the community. This condition is certainly burdensome for the foundation's owners